(untitled) (Bangladesh Journal of Urology, 2022)
Background: First reported case of penile fracture was made an Arab physician, more than 1000 years ago. Fracture penis not an uncommon genitourinary trauma, once it was thought. Sexual intercourse, masturbation, rolling over or falling onto the erect penis, abrupt blunt trauma by forceful bending of the erect penis etc. are the main causes of penile fracture. Treatment option of fracture penis now a days is operative. Materials and methods: It was a retrospective study. Patients with fracture penis admitted in the Department of Urology and Surgery Rangamati Medical College hospital and Chattogram National Hospital (Pvt.) Ltd. since May 2008 to December 2019 were included in this study. Total 9 patients were treated with fracture penis in this period of time. Patients were diagnosed by proper history, physical examination and investigations. Patients with genitourinary trauma due to other reasons were excluded from the study. Patient’s data were collected from hospital records and were analyzed later on. Results: Nine patients with fracture penis were included in this study. Six patients developed fracture during sexual intercourse, two during penile manipulation and one gave ambiguous history. After proper preoperative preparation and counselling, they underwent operation. The defect of tunica albuginea was identified and repaired. One patient had urethral injury which was also repaired at the time of repair of tunica albuginea. All the patients were evaluated post operatively. One patient had mild erectile dysfunction, others were normal. Conclusion: Immediate repair of the tunica albuginea was the corner stone of success. Bangladesh J. Urol. 2021; 24(1): 20-24